LINC00958 as new diagnostic and prognostic biomarker of childhood acute lymphoblastic leukaemia of B cells - Altieri, Filomena; Buono, Lorena; Lanzilli, Mariamichela; Mirabelli, Peppino; Cianflone, Alessandra; Beneduce, Giuliana; De Matteo, Antonia; Parasole, Rosanna; Salvatore, M.; Smaldone, Giovanni (Frontiers in Oncology, 2024)
Background: Paediatric acute B-cell lymphoblastic leukaemia is the most common cancer of the paediatric age. Although the advancement of scientific and technological knowledge has ensured a huge step forward in the management of this disease, there are 15-20% cases of recurrence leading to serious complications for the patient and sometimes even death. It is therefore necessary to identify new and increasingly personalised biomarkers capable of predicting the degree of risk of B-ALL in order to allow the correct management of paediatric leukaemia patients. Methods: Starting from our previously published results, we validate the expression level of LINC00958 in a cohort of 33 B-ALL and 9 T-ALL childhood patients, using in silico public datasets as support. Expression levels of LINC00958 in B-ALL patients stratified by risk (high-risk vs standard/medium-risk) and who relapsed 3 years after the first leukaemia diagnosis were also evaluated. Results: We identified the lncRNA LINC00958 never associated with leukaemia previously as a biomarker of B-ALL, capable of discriminating B-ALL from T-ALL and healthy subjects. Furthermore, we associated LINC00958 expression levels with the disease risk classification (high risk and standard risk). Finally, we show that LINC00958 can be used as a predictor of relapses in patients who are usually stratified as standard risk and thus not always targeted for marrow transplantation. Conclusion: Our results open the way to new diagnostic perspectives that can be directly used in clinical practice for a better management of B-ALL paediatric patients.